2019
DOI: 10.1088/1757-899x/518/6/062012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Graphene Oxide Using Simplified Hummer’s Method for Antibacterial Application

Abstract: In order to promote the biological applications of graphene based materials, great exploration for nano-scale preparation of graphene oxide (GO) has been made with a novel facile processing method and low cost. For these reasons this method has been carried out in the following study. The GO nanosheets have been prepared depending on Hummer’s method, which represents an easy and efficient technique since 1958. Alternations have been done to simplify this method in order to prepare the GO with a novel way witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Despite the sulfur residue, manganese and nitrogen impurities were not detected in the synthesized GO (Fig. 5e and f) 65,66 . The elemental analysis by XPS revealed that the contents of carbon, oxygen, and sulfur were 65.9, 33.6, and 0.4 at%, respectively.…”
Section: Characteristics Of Go From Modified Hummers' Methodsmentioning
confidence: 97%
“…Despite the sulfur residue, manganese and nitrogen impurities were not detected in the synthesized GO (Fig. 5e and f) 65,66 . The elemental analysis by XPS revealed that the contents of carbon, oxygen, and sulfur were 65.9, 33.6, and 0.4 at%, respectively.…”
Section: Characteristics Of Go From Modified Hummers' Methodsmentioning
confidence: 97%
“…Graphene Powder Synthesis. Throughout this paper, the graphene (reduced graphene oxide) used was in powder form and was produced by a modified Hummers' method, 24 which uses strong oxidants to insert guest molecules and/or ions, i.e., "oxygen-containing functional groups" having negative charges, between the graphite layers to overcome the van der Waals' forces existing between layers.…”
Section: Methodsmentioning
confidence: 99%